Capacity analysis of cognitive UWB networks - HONG Li1; MA Jun-fei 1; XU Fang-min 2; Li Shu-rong 3; ZHOU Zheng 2 (Tongxin xuebao)
The problem of analyzing the capacity of cognitive UWB networks was investigated.Taking into account of several factors such as transmission power constraints,interference temperature constraint in the receiver of primary system,outage probability and maximum allowed users were calculated by semi-analytical approach.Simulations were provided to illustrate the analysis.It is also proved that the increase of interference temperature will deteriorate the capacity of cognitive UWB network;and the constraint of interference temperature is related to the constraint of transmission power.